Pengalaman perawat melakukan kanulasi intravena pada pasien pediatrik onkologi: A literature review - Chodijah, Siti; Kartika, Lia (Holistik Jurnal Kesehatan, 2026)
Background: Peripheral Intravenous Catheter (PIVC) placement is a frequently performed nursing procedure in pediatric oncology patients. A successful first-attempt placement (FASR) is crucial to minimize pain, psychological trauma, vascular damage, and delays in treatment. However, vascular fragility due to chemotherapy, patient characteristics, and challenges in nursing clinical practice can influence the success of the first insertion. Purpose: To analyze and synthesize research findings related to nurses' experiences in achieving successful first-attempt PIVC placement in pediatric oncology patients. Method: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search strategy used the Population, Concept, and Context (PCC) framework in PubMed, MEDLINE, and Google Scholar databases. Article selection was performed using Covidence. Six articles meeting the inclusion criteria were analyzed using a thematic analysis approach. Results: Thematic synthesis yielded three main themes: (1) clinical factors and characteristics of pediatric oncology patients, (2) nurses' experiences and technical competencies, including the role of protocol-based training, and (3) technological support and organizational quality improvement interventions. Conclusion: FASR is influenced by a complex interaction between patient conditions, nurse competencies, and healthcare system support.   Keywords: Intravenous Cannulation; Nurses' Experiences; Pediatric Oncology Patients.   Pendahuluan: Pemasangan Peripheral Intravenous Catheter (PIVC) merupakan tindakan keperawatan yang sering dilakukan pada pasien pediatrik onkologi. Keberhasilan pemasangan pada upaya pertama (first attempt success rate/FASR) penting untuk meminimalkan nyeri, trauma psikologis, kerusakan vaskular, serta keterlambatan terapi. Namun, fragilitas vaskular akibat kemoterapi, karakteristik pasien, dan tantangan praktik klinis keperawatan dapat memengaruhi keberhasilan tusukan pertama. Tujuan: Untuk menganalisis dan mensintesis hasil penelitian terkait pengalaman perawat dalam mencapai upaya pertama keberhasilan pemasangan PIVC pada pasien pediatrik onkologi. Metode: Tinjauan sistematis ini mengikuti pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Strategi pencarian menggunakan kerangka Population, Concept, and Context (PCC) pada basis data PubMed, MEDLINE, dan Google Scholar. Seleksi artikel dilakukan menggunakan Covidence. Enam artikel yang memenuhi kriteria inklusi dianalisis dengan pendekatan analisis tematik. Hasil: Sintesis tematik menghasilkan tiga tema utama, yaitu: (1) faktor klinis dan karakteristik pasien pediatrik onkologi, (2) pengalaman dan kompetensi teknis perawat termasuk peran pelatihan berbasis protokol, dan (3) dukungan teknologi serta intervensi peningkatan mutu organisasi. Simpulan: FASR dipengaruhi oleh interaksi kompleks antara kondisi pasien, kompetensi perawat, dan dukungan sistem pelayanan kesehatan.   Kata Kunci: Kanulasi Intravena; Pasien Pediatrik Onkologi; Pengalaman Perawat.